2020
DOI: 10.1097/corr.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Challenges and Complications of Sterilizing Autografts with Liquid Nitrogen for Malignant Bone Tumors? A Preliminary Report

Abstract: Background Reconstruction of defects after resection of malignant bone tumors with liquid nitrogen-sterilized recycled autografts is an alternative to bone allografts and endoprostheses in resource-constrained environments. Most studies reporting favorable outcomes with liquid nitrogen-sterilized autografts for bone reconstruction are geographically restricted to a few countries, and the technical challenges of routinely using liquid nitrogen intraoperatively, especially when using the pedicle free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…We reported that liquid nitrogen kills normal and tumor tissues, and developed reconstruction methods using liquid nitrogen-treated tumor-bearing bone after wide excision of malignant bone tumors [23,29,51,53,59,60]. Furthermore, the efficacy of liquid nitrogen treatment for malignant bone tumors has been reported worldwide [19,24,36,37,47,56,58]. However, we only performed hematoxylin-eosin staining to investigate local recurrence in the midportion of the nerve.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that liquid nitrogen kills normal and tumor tissues, and developed reconstruction methods using liquid nitrogen-treated tumor-bearing bone after wide excision of malignant bone tumors [23,29,51,53,59,60]. Furthermore, the efficacy of liquid nitrogen treatment for malignant bone tumors has been reported worldwide [19,24,36,37,47,56,58]. However, we only performed hematoxylin-eosin staining to investigate local recurrence in the midportion of the nerve.…”
Section: Limitationsmentioning
confidence: 99%
“…We have developed a reconstruction method using liquid nitrogen-treated tumor-bearing bone after wide excision of malignant bone tumors [23,29,51,53,59,60]. This technique is now used worldwide [19,24,36,37,47,56,58]. We applied this freezing technique to the nerves and thought that using liquid nitrogen-treated tumor-bearing nerves for peripheral nerve reconstruction after wide excisions may provide good functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This technique also obviates the need for a bone bank or special equipment [10,16]. Its osteoinductive and osteoconductive capabilities have been shown to be superior to those of hyperthermia [4,7,16,20]. Further, Xu et al [20] studied the regeneration process in a pedicle frozen bone model in rabbits and the patterns of angiogenesis and revitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, conventional treatments like bone autografts and allografts and bone cement reconstruction have been used to repair bone defects with primary stability and long-term regeneration; however, these strategies also show some drawbacks ( Bai et al, 2020b ; Butscheidt et al, 2021 ; Chen et al, 2021 ). Among them, bone autografts are considered the gold standard for treatment of bone defects owing to the excellent osteoconduction, osteoinduction, and osteogenesis in bone regeneration ( Hindiskere et al, 2020 ). However, some disadvantages, such as donor-site morbidity, high cost, and long rehabilitation time, limit the application of bone autografts ( Boriani et al, 2017 ; Fahmy-Garcia et al, 2018 ; Lim et al, 2019 ; Han et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%